2018
DOI: 10.1007/s40265-018-0881-y
|View full text |Cite
|
Sign up to set email alerts
|

Switching Reference Medicines to Biosimilars: A Systematic Literature Review of Clinical Outcomes

Abstract: IntroductionTo evaluate the possibility that switching from reference biologic medicines to biosimilars could lead to altered clinical outcomes, including enhanced immunogenicity, compromised safety, or diminished efficacy for patients, a systematic literature review was conducted of all switching studies between related biologics (including biosimilars).MethodsA systematic search was conducted using the Medline® and Embase® databases up to 30 June 2017 employing specific medical subject heading terms. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
173
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(182 citation statements)
references
References 36 publications
(37 reference statements)
5
173
0
4
Order By: Relevance
“…Cohen et al . conducted a systematic review of switching reference medicines to biosimilars . Ninety studies were identified involving seven agents that treated 14 disease indications and enrolled a total of 14 225 individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen et al . conducted a systematic review of switching reference medicines to biosimilars . Ninety studies were identified involving seven agents that treated 14 disease indications and enrolled a total of 14 225 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…These data addressed concerns over immunogenicity, efficacy, and safety when switching from an innovator to a biosimilar biologic agent. Prospective and retrospective IBD‐specific data showed that switching to biosimilars (mostly CT‐P13, also known as Inflectra, Remsima, and infliximab‐dyyb, the first biosimilar monoclonal antibody) made no significant differences in efficacy, safety, and immunogenicity . The PROSIT‐BIO cohort: A prospective observational study of patients with IBD treated with CT‐P13 included 313 CD and 234 UC patients.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, concerns have been raised that switching from reference medicines to biosimilars may lead to increased immunogenicity and consequential safety problems, or even a loss of efficacy . Furthermore, in the setting of chronic conditions, such as immune‐mediated inflammatory disorders, patients are often scheduled to receive the same biological medicine for years.…”
Section: Discussionmentioning
confidence: 99%
“…Although prescribing biosimilars to biologic‐naive patients is well accepted, switching patients between reference and biosimilar medicines may be a concern for clinicians due to lack of clinical data and recommendations . Concerns surrounding switching to biosimilars include the possibility of increased immunogenicity, safety issues and even loss of efficacy …”
mentioning
confidence: 99%
“…The study confirmed the safety of switching a given patient from being treated with a reference product containing infliximab to being treated with a biosimilar version of the medicine. Moreover, a recent meta‐analysis of more than 90 studies, involving over 14 000 patients, confirmed that no specific risks can be attributed to the replacement of a reference medicine with a biosimilar . As highlighted in the meta‐analysis, immunogenicity is a common matter of concern for prescribers when making a switching decision.…”
mentioning
confidence: 97%